A Global History of Warfare and Technology - Roy, Kaushik. author. aut Link
XIV, 189 p. 1 illus.
Keywords: This book addresses the global history of technology, warfare and state formation from the Stone Age to the Information Age. Using a combination of top-down and bottom-up methodologies, it examines both interstate and intrastate conflicts with a focus on Eurasian technology and warfare. It shows how human agency and structural factors have intertwined, creating a complex web of technology and warfare. It also explores the interplay between technological and non-technological factors to chart the evolution of warfare from its origins to the present day, arguing that the interactions between civilian and military sectors have shaped the use of technology in warfare. Given its scope and depth, it is a valuable resource for researchers in fields such as world history, history of science and technology, history of warfare and imperialism and international relations.